THE RELATIONSHIP BETWEEN PARITY ANDMACROSOMIA BIRTH IN THE DISTRICT OF ACEH BESAR - marati, Ulyatul (Journal of Midwifery and Community Health (JMCH), 2023)
Introduction: According to the IDHS 2012, the Infant Mortality Rate (IMR) in Indonesia was 34 per 1000 births. Macrosomia is defined as birth weight >4000 g or babies larger than normal. Macrosomia is an important cause of fetal morbidity and mortality. According to the Indonesian Basic Health Research 2018, the incidence of macrosomia birth in Indonesia was 3.7 %, in Aceh Province in 2018 was 7.7%, and the prevalence of obese children in the district of Aceh Besar was 2.9%. This study aims to analyze the relationship between the parity of mother and macrosomia birth in Puskesmas Blang Bintang, the district of Aceh Besar. Methods: This study was an analytic survey study with a case-control design. It was conducted in Puskesmas Blang Bintang's work area, in the Aceh Besar district, from September 2018 to March 2019, with a total sample of 40 infants divided into two groups. Data analysis used univariate and bivariate analysis using Chi-Square Test (x ) with a 95% confidence interval. Result: There was no significant relationship between the parity of mothers,s and macrosomia births. Conclusion: The number of mothers parity did not impact macrosomia birth.